Vascular malformations: a hospital based study - Sunilkumar, Komanapalli; Aithal, Karthik; Jena, Unmesh Kumar; Prasad, Uma; Atla, Bhagyalakshmi; Sudhakar, P. V. (International Journal of Research in Medical Sciences, 2019)
Background: Vascular anomalies comprise a widely heterogeneous group of lesions. Diagnosis and management of these lesions present challenges to the surgeons, radiologists and histopathologists. Accurate classification of these lesions results in appropriate therapy. Aim of the study is to study the role of histopathology and histochemical stain in the diagnosis of vascular malformation Methods: The present study is a hospital based observational study on vascular malformations over a period of three years from 2016 to 2018 done in department of Pathology and Plastic Surgery at tertiary care centre, Visakhapatnam. Results: Out of 107 specimens of vascular anomalies received, 72 cases were vascular neoplasms, 35 were vascular malformations. Majority of the vascular malformations were seen in the cervicofacial region (43%) followed by extremities (37.1%). Most common malformation in the present study was arterio venous malformations (60%) followed by venous malformations (22.8%). Verhoeff’s VanGieson stain demonstrated discontinuity of internal elastic lamina in cases of arteriovenous malformation and helped in differentiating the lesions from capillary malformation and vascular tumors. Conclusions: Histopathology, special histochemical stains along with imaging features can be used to reduce diagnostic difficulties and in helping proper management of vascular malformations.